The JCPOA and safeguards: model or outlier?. Issue 3 (4th May 2017) - Kerr, Paul
ABSTRACT: Although the nuclear safeguards established in the 2015 Joint Comprehensive Plan of Action (JCPOA) are explicitly confined to application in Iran, some experts and policy makers have considered whether these supplementary measures could be applied to other states of proliferation concern. While the JCPOA has provided some useful additions to the International Atomic Energy Agency (IAEA) safeguards toolkit, its legacy for the broader IAEA safeguards mission is unclear. To better assess this potential legacy, this article considers the JCPOA in the context of the evolution of safeguards, particularly the developments following the 1991 Gulf War and subsequent changes to safeguards implementation in Iraq. The article then describes the JCPOA's safeguards in Iran and the potential to apply similar provisions elsewhere.